2016
DOI: 10.1111/jgs.14029
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Circulating Thyroid‐Stimulating Hormone, Free Thyroxine, and Free Triiodothyronine Concentrations and 9‐Year Mortality in Euthyroid Elderly Adults

Abstract: Objectives Thyroid dysfunction in the elderly is associated with adverse clinical outcomes, with mortality being associated with low TSH. However, it is still unknown whether variability of thyroid function test within the reference range is associated with mortality in older adults. We studied the association between plasma levels of TSH, free T3 (FT3), and free T4 (FT4), and all-cause mortality in older adults who had all three hormones within the normal range. Design Longitudinal study Setting Community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 36 publications
3
29
0
Order By: Relevance
“…A higher BMI was found to be causally related to higher circulating levels of fT3 [ 19 ], and higher BMI has also been positively associated with old age survival [ 20 ]. The lower risk of mortality with higher levels of fT3 we found was reported by others only in crude analyses when illness was not taken into account [ 18 , 21 , 22 ]. Yet, adjustment for levels of hsCRP did not materially influence the results.…”
Section: Discussionsupporting
confidence: 69%
“…A higher BMI was found to be causally related to higher circulating levels of fT3 [ 19 ], and higher BMI has also been positively associated with old age survival [ 20 ]. The lower risk of mortality with higher levels of fT3 we found was reported by others only in crude analyses when illness was not taken into account [ 18 , 21 , 22 ]. Yet, adjustment for levels of hsCRP did not materially influence the results.…”
Section: Discussionsupporting
confidence: 69%
“…In contrast with subclinical hypothyroidism, many previous studies have shown that low serum TSH is associated with poor outcomes, either increased all-cause or vascular mortality, or AF (1214, 17, 29, 36, 37). This has led to suggestions that patients with low TSH should be aggressively treated for hyperthyroidism to avoid these complications despite a complete lack of compelling (level 1) evidence to support the effectiveness of this strategy (1, 41, 42).…”
Section: Discussionmentioning
confidence: 97%
“…The most frequent abnormality found is a raised serum TSH with circulating thyroid hormone concentrations that are within reference range, correlating with the state of subclinical hypothyroidism, and some studies suggest an adverse effect of this state (8, 10, 22, 24) whereas others show a neutral or even protective effect on outcome (2, 17, 25, 29, 36, 37). Notably, the Leiden 85+ study, a cohort study of 85-year-olds with a similar design to our study, found that subclinical hypothyroidism was associated with reduced all-cause mortality and cardiovascular mortality (29).…”
Section: Discussionmentioning
confidence: 99%
“…Exploring the minimal and average TSH levels during follow-up proved a similar trend. Although several studies investigated the effects of subclinical and overt hypothyroidism on mortality, and others investigated the significance of single measurement of thyroid function tests, this is the first study to focus on levothyroxine-treated adult patients with repeated measurements of thyroid function tests (4,6,7,8,9,10,11,12,13,14,15,16,17) (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies investigated the link between subclinical and overt hypothyroidism and mortality, with conflicting results (4,6,7,8,9,10,11,12,13,14,15,16,17). Waring et al reported that a single measurement of thyroidstimulating hormone (TSH) and free T4 (fT4) did not predict the mortality in older men (7).…”
Section: Introductionmentioning
confidence: 99%